Energy-saving cooling strategies in tunnel-ventilated dairy buildings: Computational fluid dynamics (CFD) simulations and validation - Li Jiang; Yoonhong Yi; Neslihan Akdeniz (Smart Agricultural Technology)
Ventilation is a key strategy for addressing heat stress in dairy cattle. In this study, we developed computational fluid dynamics (CFD) models for a 252-head free stall tunnel-ventilated dairy building equipped with ridge openings and circulation fans. A detailed cow model was developed for a standard 625 kg Holstein cattle. Both tube and floor cooling were developed as supplemental cooling strategies using a ground source heat pump while the ventilation fans continued to operate at a reduced air speed (30 to 65 % reduction). The average air velocity within the stalls for the control (1.4 ± 0.32 m s-1) was significantly higher than the average velocity achieved with floor cooling (1.02±0.41 m s-1) and tube cooling (0.69±0.21 m s-1) (p = 0.043). Despite lower air velocities, CFD simulations showed that the average temperature at cow resting height for tube cooling (27.9 ± 0.21 °C) was significantly lower than that for the control (28.6 ± 0.36 °C) and floor cooling (28.3 ± 0.14 °C) (p = 0.021). For 252 cows, the total electricity consumption for the control was 40,590 kWh during summer, while for floor cooling, it varied between 30,683 and 36,181 kWh, and for tube cooling, it ranged from 15,879 to 21,378 kWh. Ventilation-related greenhouse gas (GHG) emissions from the tunnel-ventilated barn were 0.12 t of CO2 eq. per cow. Future studies could investigate the impact of reduced airflow rates on air quality inside the buildings.